GM-001 Role of the pharmacist in hospital: What is the perception of health professionals?. (14th February 2016) - Cheikh, A; Wartiti, M El; Enneffah, W; Cheikh, Z; Zerhouni, W; Bouatia, M; Rahali, Y; Bennana, A; El Hassani, A; Cherrah, Y
Abstract : Background: The pharmacist has a central role in a hospital. However, in the absence of regulation (law) that defines the role and prerogatives of the hospital pharmacist in developing countries, the missions of the pharmacists are many, and perceptions of other health professionals on the role played by pharmacists in hospital are disparate. Purpose: To determine the perception of health professionals about the role of the hospital pharmacist. Three questions were asked of health professionals: (1) What is the role of the pharmacist in the hospital? (2) Can we run a hospital without a pharmacist? (30 What is the perception of hospital pharmacists in relation to their missions? Material and methods: A survey was conducted among different categories of health professionals (pharmacists, physicians, nurses and technicians in three hospitals). Tables 1–3 were presented to health professionals to assess their perceptions on the role of hospital pharmacists. Results: 120 responses were collected and analysed. The results are summarised in tables 1–3. Conclusion: Procurement is the most important function performed by pharmacists in hospitals in the eyes of health professionals. Therapeutic monitoring is the least. Other tasks of the hospital pharmacist that are perceived as important include application of pharmacoeconomics rules. The pharmacist is seen by health professionals as an essential and non-essential professional for all missions selected. The regulatory prerogatives of hospital pharmacists should be more specific and clarified. The illegal practice of hospital pharmacy should be severely punished. References and/or Acknowledgements: Acknowledgements to the pharmacy team at Cheikh Zaid Hospital. No conflict of interest.